Diet and Dietary Habits of The Mystus gulio from The Cianjur Estuaries, Indonesia - Epa Paujiah; Yayat Dhahiyat; Titin Herawati; Iskandar Iskandar; Haryono Haryono; Iwang Gumilar (UIN Sunan Gunung Djati Bandung, 2023)
Food and feeding habits are important things in bioecological of fish. This study provides an understanding of the feeding habits and intensity of the M. gulio, by analyzing its food composition, relative gut length (RGL) and gastro-somatic index (GaSI). Fish specimens were caught with a gill net and fishing rod in an area of Cianjur estuaries during a period of one year from October 2021 to September 2022. The analysis of 452 fish samples shows that the relative gut length (RGL) values revealed the feeding habit of M. gulio as carni-omnivorous. The GaSI value was used to determine feeding intensity and was found to be highest in November, at Cidamar estuary, and in the second size group (7.1-10 cm). These results provide new knowledge on this fish species’ feeding habit and intensity, which also helps understand the fish adaptation and conservation in the study area.